Increasing Community Awareness and Intention in Encouraging The Growth of Cash Waqf - Muhammad Iqbal; Prameswara Samofa Nadya; Saripudin Saripudin; Puji Hadiyati (Economica: Jurnal Ekonomi Islam, 2019)
This study aims to identify factors that determine the awareness, intention and decision of the Indonesian people to cash waqf. Data collection techniques using purposive sampling with PLS (Partial Least Squared) method as a data analysis tool in this study includes a path analysis model. The results obtained show that the social environment and understanding affect one's awareness and interest in cash waqf. The emergence of awareness and intention will encourage the person to carry out cash waqf. While the promotion of cash waqf does not affect awareness and intentions which in the end will not encourage someone to cash waqf.Penelitian ini bertujuan mengidentifikasi faktor-faktor yang menentukan kesadaran, minat dan keputusan masyarakat Indonesia untuk berwakaf uang. Teknik penggumpulan data menggunakan purposive sampling dengan metode PLS (Partial Least Squared) sebagai alat analisis data yang dalam penelitian ini memuat model analisis jalur. Hasil yang diperoleh menunjukkan bahwa lingkungan sosial dan pemahaman mempengaruhi kesadaran dan minat seseorang akan wakaf uang. Munculnya kesadaran dan minat akan mendorong orang tersebut untuk melaksanakan wakaf uang. Sedangkan promosi tentang wakaf uang tidak mempengaruhi kesadaran dan minat yang pada akhirnya tidak akan mendorong seseorang untuk berwakaf uang.